Effect of Visuospatial Attention on the Sensorimotor Gating System - Ishii, Daisuke; Takeda, Kotaro; Yamamoto, Satoshi; Noguchi, Akira; Ishibashi, Kiyoshige; Tanamachi, Kenya; Yozu, Arito; Kohno, Yutaka (Frontiers in Behavioral Neuroscience, 2019)
The integration of multiple sensory modalities allows us to adapt to the environment of the outside world. It is widely known that visual stimuli interfere with the processing of auditory information, which is involved in the ability to pay attention. Additionally, visuospatial attention has the characteristic of laterality. It is unclear whether this laterality of visuospatial attention affects the processing of auditory stimuli. The sensorimotor gating system is a neurological process, which filters out unnecessary stimuli from environmental stimuli in the brain. Prepulse inhibition (PPI) is an operational measure of the sensorimotor gating system, which a weaker prestimulus (prepulse), such as a visual stimulus, inhibits the startle reflex elicited by a subsequent robust startling stimulus (pulse) such as a tone. Therefore, we investigated whether the visual stimulus from the left or right visual space affects the sensorimotor gating system in a “rest” task (low attentional condition) and a “selective attention” task (high attentional condition). In the selective attention task, we found that the target prepulse presented in the left and bilateral visual fields suppressed the startle reflex more than that presented in the right visual field. By contrast, there was no laterality of PPI in the no-target prepulse condition, and there was no laterality of PPI in the rest task. These results suggest that the laterality of visuospatial attention affects the sensorimotor gating system depending on the attentional condition. Moreover, the process of visual information processing may differ between the left and right brain.